Design and development of a bowling machine for effective and efficient cricket batting training / Buddhika Sampath Kumara ... [et al.] - Kumara, Buddhika Sampath; Samarathunga, Amalka Indupama; Vithanage, Vimukkthi; Ranawaka, Najitha Dewmith; Gunwardane, Sameera Sampath; Mangala, Janaka; Chathuranga, Damith Suresh; Punchihewa, Himan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
Cricket is one of the most popular sports in the world. For the batters to practice, there could be a requirement for an effective and efficient device to mimic different bowling variations to enhance the training sessions. This research consists of computer aided design, simulation, and fabrication of a robust cricket bowling machine to achieve target bowling for effective training of cricket batters. A novel ball propelling mechanism was designed with two degrees of freedom movements of a pair of rotating wheels. Mechanisms for sudden speed changes were also tested with prototypes during this design. However, for acceptable product compactness and cost, the design was prototyped without the sudden speed changing concept. The base is maintained on a bi-axial precise tilting gyroscopic mechanism. This tilting mechanism accurately adjusts the delivery point of the ball with respect to a two-axis system, which helps to control the line and length of the ball. The novel ball propelling mechanism enhances the stability of controlling in pitching position, ball rotation axis, and ball speed. Controlling these parameters effectively creates an environment for efficient practice sessions for batsmen. Target bowling is the main objective of this study and the machine intends to mimic the vast bowling variations.